Structural and Functional Characterization of a Testicular Long Non-coding RNA (4930463O16Rik) Identified in the Meiotic Arrest of the Mouse Topaz1–/– Testes - Chadourne, Manon; Poumerol, Elodie; Jouneau, Luc; Passet, Bruno; Castille, Johan; Sellem, Eli; Pailhoux, Eric; Mandon-Pépin, Béatrice (Frontiers in Cell and Developmental Biology, 2021)
Spermatogenesis involves coordinated processes, including meiosis, to produce functional gametes. We previously reported Topaz1 as a germ cell-specific gene highly conserved in vertebrates. Topaz1 knockout males are sterile with testes that lack haploid germ cells because of meiotic arrest after prophase I. To better characterize Topaz1–/– testes, we used RNA-sequencing analyses at two different developmental stages (P16 and P18). The absence of TOPAZ1 disturbed the expression of genes involved in microtubule and/or cilium mobility, biological processes required for spermatogenesis. Moreover, a quarter of P18 dysregulated genes are long non-coding RNAs (lncRNAs), and three of them are testis-specific and located in spermatocytes, their expression starting between P11 and P15. The suppression of one of them, 4939463O16Rik, did not alter fertility although sperm parameters were disturbed and sperm concentration fell. The transcriptome of P18-4939463O16Rik–/– testes was altered and the molecular pathways affected included microtubule-based processes, the regulation of cilium movement and spermatogenesis. The absence of TOPAZ1 protein or 4930463O16Rik produced the same enrichment clusters in mutant testes despite a contrasted phenotype on male fertility. In conclusion, although Topaz1 is essential for the meiosis in male germ cells and regulate the expression of numerous lncRNAs, these studies have identified a Topaz1 regulated lncRNA (4930463O16Rik) that is key for both sperm production and motility.